Strategi Komunikasi Pariwisata - Sang Ayu Made Rahayu; I Gede Sutarya; Ni Nyoman Perni (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
This study aims to examine the form of tourism marketing communication strategies carried out by the Bali Provincial Tourism Office in an effort to increase foreign tourist visits to Bali. This research was conducted at the Bali Provincial Tourism Office. The sample in this study was selected by purposive sampling method. In this study, several data collection techniques were used, including observation, interviews, literature study, and documentation. So that the data analysis technique in this study is all data that has been analyzed since observation and in-depth interviews, described, classified, analyzed and interpreted according to the research to be carried out so that the results obtained are truly accountable and a broader understanding of tourism marketing communication is obtained. in increasing foreign tourist visits to Bali. From the results of data analysis, it was found that the marketing communication strategy carried out by the Bali Provincial Tourism Office optimizes promotions through social media as well as with cultural-based events with local wisdom which is a typical Balinese series, tourism communication is carried out by designing promotions through optimizing social media to distributing promotional tools that have been designed in the form of videos, posters, and so on during the covid-19 pandemic with restrictions on existing activities and the implications of the tourism communication strategy that is being carried out, namely the reach of promotions is becoming wider and making the promotions effective and efficient.